KONTRIBUSI POWER OTOT TUNGKAI DAN KOORDINASI MATA-TANGAN DENGAN KETERAMPILAN PUKULAN SMASH DALAM PERMAINAN BOLA VOLI TIM PUTRA PERTAMINA HULU ENERGI KAMPAR - Habibi Bima Sakti; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Smash is one of playing technique in volleyball. A good smash needs a fit body condition. Based on observation, researcher found that player in attack zone always does mistake when they are doing a smash. This mistake considered happen because of there is no muscular leg power to reach ball as high as possible and a good eye-hand coordination when doing smash. The goal of this research is to know about contribution of muscular leg power and eye-hand coordination to smash hit skill in volleyball game of Pertamina Hulu Energi Kampar man team. This research contains of three variables which are; leg muscular power (X1), eye-hand coordination (X2), and smash hit skill (Y). The sample took the whole sample (total sampling) of Pertamina Hulu Energi Kampar volleyball man team that contains of 10 athletes. The data collected by using vertical power jump instrument, throw and catch tennis ball, and spike or smash test. Data processing used correlation method which using normality test, correlation of product-moment test, and contribution deciding. The normality test of variable X1, L0max (0,126) < Ltable (0,258), normality test of variable X2, L0max (0,212) < Ltable (0,258), and normality test of variable Y, L0max (0,148) < Ltable (0,258). On significant stage of 0,05 if L0maks < Ltabel means the population distributed normally. The product-moment test of X1Y Rhitung (-0,29) < Rtabel (0,666) with contribution about 8,41%, the product-moment test of X2Y Rhitung (0,14) < Rtabel (0,666) with contribution about 1,96%, and product-moment test of X1X2Y Rhitung (0,08) < Rtabel (0,666) with contribution about 0,64%. As seen at interpretation table of correlation coefficient, the trial of all hypothesis lay in “very low” relation. But, there is still contribution from all of hypothesis trial.Keywords :Smash, research test, correlation